Capture‐Transport Double Enhancement Strategy to Construct High‐efficiency Photo‐catalysts with p‐n Junction for Hydrogen Production under Visible‐light Irradiation. Issue 27 (15th July 2022) - Chen, Yanyan; Yu, Minghui; Yu, Hao; Wang, Shuang; Cheng, Yuye; Dou, Minghao; Gong, Xiaoyu; Li, Zhiqiang; Shao, Hongyu; Li, Shenjie
Abstract: The conversion of solar energy into chemical energy by photo‐hydrolysis is considered as an effective way to solve current energy and environmental problems. The preparation of photo‐catalysts with excellent activity is expected to promote the rapid development of photo‐catalytic hydrogen production research. A two‐step strategy is used to obtain a CdS‐based photo‐catalyst with enhanced photo‐hydrogen production efficiency by improving the electron transport efficiency and the intrinsic electric field to promote electron separation. The CdS/Ag2 S/NiS nanocomposites were prepared by a two‐step method in this work. After characterization of the structure, optical properties and surface chemical state by XRD, EDS, XPS, TEM and UV‐vis, it is found that Under visible light exposure (λ=420 nm), when the ratio of NiS is 11 %, the sample got the highest hydrogen yield (3280 μmol ⋅ g −1 ⋅ h −1 ), which is 2.8 times of CdS/Ag2 S material, and also showing good cycle stability. The improved catalytic efficiency can be attributed to two points: the introduction of Ag2 S provides more electro‐chemical active sites and routes for nano‐materials; the introduction of NiS builds an internal electric field to promote the transmission and separation of optical electrons and holes, and improve aquatic hydrogen capacity. Abstract : Photocatalytic hydrogen production is considered to serve as an effective way to solve current energy and environmental problems. Through a two‐step approach, Ag2 S is introduced to provide more electrochemical active sites for nanomaterials, and then NiS is introduced to establish an internal electric field to improve the transport and separation of optical electrons and holes, improving the capacity of aquatic hydrogen. This strategy provides possible and guidance for the construction of highly efficient composites.